Effects of EAS cochlear implantation surgery on vestibular function. (November 2013) - Tsukada, Keita; Moteki, Hideaki; Fukuoka, Hisakuni; Iwasaki, Satoshi; Usami, Shin-ichi
Abstract Conclusions: The patients who received electric acoustic stimulation (EAS) cochlear implantation had relatively good vestibular function compared with the patients who did not have residual hearing. The vestibular function was well preserved after atraumatic EAS surgery. The round window approach and soft electrode are preferred to decrease the risk of impairing vestibular function. Objectives: The aim of this study was to examine the characteristic features of vestibular functions before and after implantations in patients undergoing EAS. Methods: Vestibular functions in patients who underwent EAS implantation were examined by caloric testing and vestibular evoked myogenic potential (VEMP) in 11 patients before and in 13 patients after implantation. Results: Preoperative evaluation showed that of the 11 patients, most (73%) had good vestibular function. One of 11 patients (9%) had decreased response in postoperative VEMP but all of the patients had unchanged results in postoperative caloric testing.